2017
DOI: 10.5204/ssj.v8i1.362
|View full text |Cite
|
Sign up to set email alerts
|

Navigating social integration into university on Facebook: Insights from a longitudinal study

Abstract: This article reports on the experiences of 26 first year students as they record on Facebook snapshots of their experiences navigating social integration into university. There is still a substantial gap in student transition success research conceptually framed by the understanding that first year transition is about becoming. Transition as becoming expands current conceptions of transition by situating it within the real world rather than just within university. Facebook status updates were used as data beca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…However, others (Park et al, 2009) found a positive relationship between the intensity of involvement in a Facebook group and levels of offline civic participation. Barnes (2017) explored the experiences of 26 first year students through their Facebook statuses at four key points during their transition into university: orientation week, first assignment, end of first semester, end of academic year. The study focused on how first year students used Facebook to navigate their social integration into university.…”
Section: Influence Of Social Media On Students' Offline Engagementmentioning
confidence: 99%
“…However, others (Park et al, 2009) found a positive relationship between the intensity of involvement in a Facebook group and levels of offline civic participation. Barnes (2017) explored the experiences of 26 first year students through their Facebook statuses at four key points during their transition into university: orientation week, first assignment, end of first semester, end of academic year. The study focused on how first year students used Facebook to navigate their social integration into university.…”
Section: Influence Of Social Media On Students' Offline Engagementmentioning
confidence: 99%
“…Previous work has highlighted how social media can facilitate students’ transition to university. We focus on this transition as a social one, through which students ‘learn the university lifestyle’ (Barnes, 2017: p. 2), rather than a physical or academic transition (Dyer, 2020). Thomas et al (2017) interviewed students about their transition to university, mapping social media changes in the week before and the five weeks after their move.…”
Section: Introductionmentioning
confidence: 99%
“…The impact of social media (SM) on business should not be underestimated as trends and a number of studies (e.g. Jacobs & Nakata, 2010;Universal McCann, 2008;Barnes, & Matson, 2008;SME Annual Report, 2007;Nielsen Company, 2010) have shown that SM, especially Facebook and Twitter, have been utilised extensively as business and marketing tools all over the world. Many studies in the United States and Europe have provided evidence that SM has a positive impact on business, especially for small and medium enterprises or SMEs (Swallow, 2010: Lesley, 2012Darban & Wei Li, 2012).…”
Section: Introduction and Background Of Studymentioning
confidence: 99%